1992
DOI: 10.1016/0378-1097(92)90414-j
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and sequence analysis of the gene coding for the 57-kDa major soluble antigen of the salmonid fish pathogen Renibacterium salmoninarum

Abstract: The complete sequence coding for the 57-kDa major soluble antigen of the salmonid fish pathogen, Renibacterium salmoninarum, was determined. The gene contained an opening reading frame of 1671 nucleotides coding for a protein of 557 amino acids with a calculated M(r) value of 57,190. The first 26 amino acids constituted a signal peptide. The deduced sequence for amino acid residues 27-61 was in agreement with the 35 N-terminal amino acid residues determined by microsequencing, suggesting the protein is synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
1

Year Published

1994
1994
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 24 publications
3
34
1
Order By: Relevance
“…Taken together these results suggests that p57 is autoproteolytic (Barton et al 1997). Sequence analysis of p57 is consistent with this possibility as there is homology between the second repeated region of p57 and both trypsin-like and V8 staphylococcal-type serine proteases (Chien et al 1992). In addition, a consensus serine protease motif G-X-S-X-G has been located from Gly-406 and Gly-4 10 between repeats B2 and B3 ( Fig.…”
Section: Fraction (Ml)supporting
confidence: 60%
See 2 more Smart Citations
“…Taken together these results suggests that p57 is autoproteolytic (Barton et al 1997). Sequence analysis of p57 is consistent with this possibility as there is homology between the second repeated region of p57 and both trypsin-like and V8 staphylococcal-type serine proteases (Chien et al 1992). In addition, a consensus serine protease motif G-X-S-X-G has been located from Gly-406 and Gly-4 10 between repeats B2 and B3 ( Fig.…”
Section: Fraction (Ml)supporting
confidence: 60%
“…P57 was partially purified and eluted with a M, of 46 500 consistent with a monomeric structure. The estimated relative molecular mass was smaller than the molecular mass of 54 505 Da calculated from the amino acid sequence of the mature protein (Chien et al 1992). The reason for this discrepancy is unknown.…”
Section: Fraction (Ml)contrasting
confidence: 56%
See 1 more Smart Citation
“…Recent studies have demonstrated that the proteolytic degradation of p57 generates most, if not all, of the immunoreactive components of R. salmoninarum ECP and p57 may possess an autoproteolytic activity (Griffiths & Lynch 1991). The N-terminal sequence of p57 has been determined and gene msa encoding this protein has now been cloned and sequenced (Chien et al 1992). The aim of this study was to generate a source of recombinant p57 protein in order to remove the timeconsuming dependence upon in vitro cultures of R. salmoninal-urn.…”
mentioning
confidence: 99%
“…From the sequence available for Renibacteriun~ salmoninarum gene msa (Chien et al 1992) 2 restriction sites close to the initiation codon were identified as suitable for the construction of translational fusions using the pMAL system for the production of maltosebinding protein (MBP) fusions (New England BioLabs): HpaI located at nucleotide 180 and StuI located at nucleotide 228. The HpaI truncated gene would encode a product of 513 amino acids and 49795 molecular weight, whilst the StuI truncated gene would encode 497 amino acids of 47 613 molecular weight.…”
mentioning
confidence: 99%